Click chemistry in carbon nanoreactors - Rance, Graham A.; Solomonsz, William A.; Khobystov, Andrei N. (Royal Society of Chemistry, 2013)
Copper-nanoparticle catalytic centres anchored at the 5 graphitic step-edges within hollow carbon nanoreactors exhibit superior activity and stability in cycloaddition reactions as compared to catalytic centres outside the nanoreactors. Nanoscale confinement enables efficient recycling of the catalyst in preparative-scale synthesis without 10 significant changes in activity.